The Ecologist's Career Compass: A game to explore career paths - Itescu, Yuval; Bernard‐Verdier, Maud; Moesch, Simon S.; Mrugała, Agata; Mrugała, Kinga; Musseau, Camille L.; Jeschke, Jonathan M. (Ecology and evolution, 2022)
One of the most challenging endeavors for students is choosing a career path that best fits their interests, wills and skills, and setting their professional goals accordingly. Such decisions are often made from within the culture of academia, in which mentors and peers are mainly familiar with the academic job market and lack the knowledge necessary to consult about other types of careers. We aimed to address this gap for ecology and related fields by creating an engaging and effective tool to help students and professionals to familiarize themselves with the diversity of potential career paths available to ecologists. The tool is an applied card game – the Ecologist's Career Compass – which is provided here freely. The game is played as a trump card game and includes 33 cards, each representing a combination of one of four job‐market sectors and one of nine types of positions. Each card indicates the level of seven skill categories required to likely be hired and succeed in the focal position at the focal sector, as well as more specific examples for typical jobs in the focal combination. The information in the game largely relies on input from a global survey we conducted among 315 ecologists from 35 countries. While the challenges faced by early‐career ecologists in developing their professional path are substantial and diverse, this game can assist in gaining a broad comparative overview of the whole ecology job market and the skills required to likely excel in different paths. We hope this applied game will act as a conversation starter about the diversity of aspirations and opportunities in ecology classrooms and labs. We conceived and designed an applied card game that provides players with a fun tool for acquiring knowledge about the possible career paths in ecology across all employment sectors and the skills required to likely be hired and succeed in each path. We aimed to build a tool that will also aid academic mentors in advising their ecology students about career development.